A-95 The Relationship between Attention Deficit Hyperactivity Disorder (ADHD) and Vestibular Impairments Following Adolescent Sports-Related Concussion (SRC). (30th August 2021) - Gilliland, Taylor; Reynolds, Erin; Covert, Kayla; Bennett, Monica; Driver, Simon
Abstract: Objective: Athletes with ADHD may experience longer and/or more complicated recoveries following SRC; however, previous research has focused on neurocognitive outcomes. The objective of this study was to investigate the relationship between a history of ADHD among adolescent athletes and vestibular impairments following SRC. Method: Participants included 166 athletes aged 15.9 +/− 1.5 who sustained an SRC, including 25 with a documented history of ADHD. Appropriate summary statistics were used to describe the data. ADHD and non-ADHD groups were compared using t-tests and Mann–Whitney U tests for continuous variables and Chi-square tests for categorical variables. A linear regression model analyzed the relationship between a history of ADHD and vestibular outcomes including horizontal and vertical vestibulo-ocular reflex (hVOR; vVOR), visual motion sensitivity (VMS), and Dizziness Handicap Index (DHI), while referral to vestibular therapy (VT) was analyzed using logistic regression. Results: Athletes with ADHD experienced significantly higher rates of on-field dizziness, (p = 0.039) and dizziness following vVOR testing on the Vestibular/Ocular Motor Screening (VOMS; p = 0.041). Athletes with ADHD were more likely to be referred to vestibular therapy (VT) (p = 0.033) and displayed abnormal vVOR test during the initial VT visit (p = 0.040). Conclusions: Adolescent athletes with a history of ADHD are more likely to report on-field dizziness following SRC and increased dizziness with vVOR testing on VOMS, thus resulting in more frequent referrals to VT, where they also display abnormal vVOR results. Additional research is needed to improve treatment strategies and recovery outcomes in athletes after SRC.